Modeling, simulation and analysis of a securities settlement system: The case of Central Securities Depository of Mexico - Muñoz, David F. (2012)
The Instituto para el Depósito de Valores (INDEVAL) is the Central Securities Depository of Mexico. It is the only Mexican institution authorized to perform, in an integrated manner, the activities of safe-keeping, custody, management, clearing, settlement and transfer of securities. In this article, we report the modeling, simulation and analysis of a new Securities Settlement System (SSS) implemented by INDEVAL, as part of a project for the implementation of a safer and more efficient operating system. The main objective of this research was to use reduced amounts of cash and securities, within reasonable periods of time, for the settlement of securities of the Mexican market. A linear programming model for the netting and clearing of operations was used. The performance of the new SSS was evaluated by performing experiments using a deterministic simulation model under different operation parameters, such as the number and monetary value of transactions, the time between clearing cycles and also under a new set of rules for pre-settlement operations. The results presented may be used by other Central Securities Depositories to make decisions related to the efficient and safer use of their resources. The implementation of the model took more than three years. Now many transactions that would remain pending if processed individually are settled together, thus reducing liquidity requirements dramatically —by 52% in cash and 26% in securities. DOI: https://doi.org/10.1016/S2077-1886(12)70007-0